2015
DOI: 10.1371/journal.pone.0119837
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Sensitive Epigenetic Regulation of an Antisense-Oriented lncRNA Controls WT1 Expression in Myeloid Leukemia Cells

Abstract: WT1 is a transcription factor expressed in hematopoietic stem cells and in most cases of myeloid leukemia. We investigated the roles of hypoxia and epigenetics in the regulation of WT1 expression in myeloid leukemia cells. WT1 expression correlates with hypomethylation of the CpG island in Intron 1, and pharmacologic demethylation of this CpG island induces WT1 mRNA expression. Hypoxia causes decreases in DNMT expression and activity and increased expression and activity of TET2 and TET3, resulting in demethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 35 publications
1
47
0
Order By: Relevance
“…Melanocytes are specialised cells that are responsible for the production of melanin, an important skin chromophore (Abdel-Malek et al, 2000;McCarty and Loeb, 2015;Ratajczak-Wrona et al, 2009). Normal skin physiology includes an epidermal-melanin unit, comprised of keratinocytes and melanocytes arranged at a ratio 35:1, the function of which is to produce melanin to protect keratinocytes from the harmful effects of environmental stressors Costin and Hearing, 2007).…”
Section: Keratinocytes and The Epidermal-melanin Unitmentioning
confidence: 99%
“…Melanocytes are specialised cells that are responsible for the production of melanin, an important skin chromophore (Abdel-Malek et al, 2000;McCarty and Loeb, 2015;Ratajczak-Wrona et al, 2009). Normal skin physiology includes an epidermal-melanin unit, comprised of keratinocytes and melanocytes arranged at a ratio 35:1, the function of which is to produce melanin to protect keratinocytes from the harmful effects of environmental stressors Costin and Hearing, 2007).…”
Section: Keratinocytes and The Epidermal-melanin Unitmentioning
confidence: 99%
“…As lncRNAs have emerged as important participants in the pathogenesis and disease progression of AML, [66][67][68][69][70][71][72][73][74] it is likely that profiling of their expression would have significant impact on MDS prognostication. Recently, it has been shown that lncRNA expression signatures were closely associated with specific mutations and a small subset of lncRNAs could predict clinical outcome in cytogenetically normal elderly AML patients, 75 but the clinical significance of lncRNA profiling in MDSs has not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression profiling of mRNA levels had been found to outperform the traditional parameters, such as morphology and cytogenetics, in prognostication of MDSs whether CD34 1 selected cells [62][63][64] or unsorted bulk marrow cells 65 were used for analysis. As lncRNAs have emerged as important participants in the pathogenesis and disease progression of AML, [66][67][68][69][70][71][72][73][74] it is likely that profiling of their expression would have significant impact on MDS prognostication. Recently, it has been shown that lncRNA expression signatures were closely associated with specific mutations and a small subset of lncRNAs could predict clinical outcome in cytogenetically normal elderly AML patients, 75 but the clinical significance of lncRNA profiling in MDSs has not yet been reported.…”
Section: Discussionmentioning
confidence: 99%